Cellulose acetate based electrolyte characterization for application in polymer electrolyte / Siti Fadzilah Ayub - Ayub, Siti Fadzilah (Research Management Institute (RMI), 2011)
Cellulose acetate film containing salt and plasticizer cellulose acetate-salt complexes was used to obtain some insight on mechanism of ionic conductivity in cellulose acetate-based polymer electrolytes. In this study, cellulose acetate film is largely amorphous. Mobile ions, NH/ from NH4CF3SO3 are contributing for ionic conductivity in the system. The number of mobile ions can be increase by plasticizer. Plasticizer can dissociate the salts which lead to ionic conductivity enhancement. The conductivity was calculated from bulk impedance obtained through impedance spectroscopy. The dielectric constant and dielectric loss versus frequency tend to a maximum at low frequency. The "long tail" feature was shown from graph modulus of imaginary and real parts of electrical modulus of sample. This feature can be attributed to high capacitance and support the plasticizer role as an agent to dissociate the salt into ions.